Introduction (Itinera, 2015)
Multiform witness of the power of language, the myth reveals itself as a privileged form of investigation of the human and its transformations. With this introduction we want to start a journey of mythological research that, overcoming the sterile reduction of the myth to mere expression of a pre-scientific and pre-rational mentality, moves in search of the core of truth hidden under the surface of the "fairy tale".